Gambaran Kepuasan Ibu Hamil terhadap Layanan Kesehatan Ibu dan Anak di Puskesmas Golowelu, Kabupaten Manggarai Barat - Violia N. K Putri; Dominirsep O. Dodo; Masrida Sinaga (Yayasan Literasi Sains Indonesia, 2025)
Satisfaction of pregnant women towards maternal and child health services is one of the important indicators in evaluating the quality of health services. The satisfaction of pregnant women has a close relationship with the quality of service provided and is measured from five dimensions of service quality, namely tangibels, responsiveness, reliability, empathy, and assurance The purpose of this study was to determine the level of satisfaction of pregnant women towards maternal and child health services based on five dimensions of satisfaction. The research method used was descriptive quantitative, with a sample size of 49 pregnant women in the working area of Golowelu Community Health Center. Data analysis used univariate analysis. Based on the research results, it was found that the satisfaction of pregnant women towards maternal and child health services at Golowelu Community Health Center based on the tangibles dimension, most pregnant women stated that they were quite satisfied (75.5%). The reliability dimension, most stated that they were very satisfied (93.9%). The empathy dimension, most stated that they were quite satisfied (91.8%). The assurance dimension, most stated that they were very satisfied (98%), and the responsiveness dimension, most stated that they were very satisfied (91.8%). Maternal and child health services at Golowelu Community Health Center have met the standards of satisfaction among pregnant women, particularly in the dimensions of reliability, assurance, and responsiveness. However, improvements are still needed in the dimensions of tangibles and empathy.